(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: During pregnancy, most of the iron endowment occurs in third trimester; so preterm infant are deprived of iron which leads to anaemia of prematurity. The problems associated with anaemia in preterm babies as well as its treatment (blood transfusion) are multiple and involve significant risks. Anaemia hinders normal growth and contributes to postnatal malnutrition in most low birth weight preterm neonates who are hospitalised for a long time. Delayed cord clamping in preterm infants results in an 8% to 24% increase in blood volume.This extra amount of blood may increase haemoglobin as well as iron content in preterm neonates. Objective: To observe the effect of timing of cord clamping on iron status of preterm neonates. Methods: It is a prospective randomized control trial. Total 40 preterm neonates of gestational age of less than 37 weeks were included in this study, they were allocated in Early Cord Clamping (ECC) group and Delayed Cord Clamping (DCC) group by random sampling technique. To estimate iron status in both groups at neonatal period, blood was collected to measure Hb, MCV, TIBC, serum iron, ferritin at 24 hrs of age and at 28 days of age. Results: This study shows that there is significant high Hb, iron and ferritin levels in delayed cord clamping group of preterm neonates. The results of Hb, serum iron and ferritin levels at 24hrs of age in ECC group were 16.53(±2.13)g/dl, 52.20(±38.78)?g/dl and 127.63(±57.45)?g/L, these parameters in DCC group were 18.65(±2.08)g/dl, 84.35(±35.03)?g/l and 188.88(±107.58)?g/L respectively.These results were significant with the p value of <0.05. These results were also significant at 28 days of life. But regarding Mean Corpuscular Volume (MCV) and Total Iron Binding Capacity (TIBC) parameters, they were not significant either in day 1 or in day 28. Conclusion: Delayed cord clamping improves iron status in preterm neonates status in early versus delayed cord clamping groups of preterm neonates delivered in certain referral hospital. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014